The New encyclopedia Britannica. - Encyclopedia Britannica, Inc. (Chicago : Encyclopedia Britannica, 2007)
Contents: v. 1-12. Micropaedia: ready reference - - v. 13-29. Macropaedia: Knowledge in depth - - [v. 30] Propaedia: outline of knowledge and guide to the Britannica. [v. 31-32] Index.
Includes bibliographical references and index
Keywords: Encyclopedias and dictionaries; English Language -- Dictionaries; Atlases